Sedimentary Nitrogen and Sulfur Reduction Functional-Couplings Interplay With the Microbial Community of Anthropogenic Shrimp Culture Pond Ecosystem - Zhou, Renjun; Hou, Dongwei; Zeng, Shenzheng; Wei, Dongdong; Yu, Lingfei; Bao, Shicheng; Weng, Shaoping; He, Jianguo; Huang, Zhijian (Frontiers in Microbiology, 2022)
Sediment nitrogen and sulfur cycles are essential biogeochemical processes that regulate the microbial communities of environmental ecosystems, which have closely linked to environment ecological health. However, their functional couplings in anthropogenic aquaculture sedimentary ecosystems remain poorly understood. Here, we explored the sediment functional genes in shrimp culture pond ecosystems (SCPEs) at different culture stages using the Geochip gene array approach with 16S amplicon sequencing. Dissimilarity analysis showed that the compositions of both functional genes and bacterial communities differed at different phases of shrimp culture with the appearance of temporal distance decay (P < 0.05). During shrimp culture, the abundances of nitrite and sulfite reduction functional genes decreased (P < 0.05), while those of nitrate and sulfate reduction genes were enriched (P < 0.05) in sediments, implying the enrichment of nitrites and sulfites from microbial metabolism. Meanwhile, nitrogen and sulfur reduction genes were found to be linked with carbon degradation and phosphorous metabolism (P < 0.05). The influence pathways of nutrients were demonstrated by structural equation modeling through environmental factors and the bacterial community on the nitrogen and sulfur reduction functions, indicating that the bacterial community response to environmental factors was facilitated by nutrients, and led to the shifts of functional genes (P < 0.05). These results indicate that sediment nitrogen and sulfur reduction functions in SCPEs were coupled, which are interconnected with the SCPEs bacterial community. Our findings will be helpful for understanding biogeochemical cycles in anthropogenic aquaculture ecosystems and promoting sustainable management of sediment environments through the framework of an ecological perspective.